Facial-aging app availability in waiting rooms as a potential opportunity for skin cancer prevention - Brinker, Titus Josef; Schadendorf, Dirk (JAMA dermatology, 2018)
This survey study explores whether a single exposure of adult patients in a waiting room to an app that approximates facial UV damage may lead to altered UV protection behavior.
Gesehen am 12.09.2019